2014
DOI: 10.1007/s00704-014-1304-y
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability patterns of the world’s total column water content: Amazon River basin

Abstract: Global trend patterns of yearly mean total column water (TCW) from the European Centre for Medium Range Weather Forecasts (ECMWF) 20th century atmosphere model ERA-20CM (1900–2009) and the currently state-of-the-art reanalysis ERA-Interim (1979–2012) show common features of statistically significant upward trends. Of particular interest appears a pronounced regional dipole pattern of interannual climate variability over the South American continent particularly evident in ERA-Interim data. The trend dipole aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…It is those basin‐wide numbers which are the basis of our assertion of an intensification of the Amazon hydrological cycle, while the spatial patterns (Figure ) serve to show where the increases happened. We also find a positive trend of water vapor content above the basin (Figure d) which has most recently been reported also by Bordi et al [], as well as over the northern tropical Atlantic (not shown, region examined: latitude range: 1.5°N, …, 31.5°N and longitude range: 298.5°E, …, 328.5°E). This latter trend is also seen in stand‐alone remote sensing data [ Santer et al , ] and is consistent with expectations given recent tropical Atlantic surface warming (Figure d).…”
Section: Recent Amazon Climate Patternssupporting
confidence: 91%
“…It is those basin‐wide numbers which are the basis of our assertion of an intensification of the Amazon hydrological cycle, while the spatial patterns (Figure ) serve to show where the increases happened. We also find a positive trend of water vapor content above the basin (Figure d) which has most recently been reported also by Bordi et al [], as well as over the northern tropical Atlantic (not shown, region examined: latitude range: 1.5°N, …, 31.5°N and longitude range: 298.5°E, …, 328.5°E). This latter trend is also seen in stand‐alone remote sensing data [ Santer et al , ] and is consistent with expectations given recent tropical Atlantic surface warming (Figure d).…”
Section: Recent Amazon Climate Patternssupporting
confidence: 91%
“…(2014); Bordi et al (2014) and Bianchi et al (2016a). Moreover, this effect can also affect other variables.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the authors also highlight that the models overestimate IWV for sites near the sea. Bordi et al (2014) studied global trend patterns of a yearly mean of IWV from ERA-20CM and ERA-Interim. The authors highlight a regional dipole pattern of inter-annual climate variability over South America from ERA-Interim data.…”
mentioning
confidence: 99%
“…The values of columnar integrated content of water vapor (IWV) as reanalysis products from ERA-Interim (Dee et al, 2011) and MERRA-2 (GMAO, 2015;Bosilovich et al, 2015;Gelaro et al, 2017) were evaluated in this study. The horizontal resolutions are 0.25 • × 0.25 • for ERA-Interim and 0.625 • × 0.50 • for MERRA-2.…”
Section: Iwv From Nwmmentioning
confidence: 99%
“…Additionally, MERRA-2 assimilates observations not available to MERRA and reduces bias and imbalances in the water cycle (Gelaro et al, 2017). Moreover, the longitudinal resolution of MERRA-2 data is changed from 0.667 • in MERRA to 0.625 • , whereas the latitudinal resolution remains unchanged (0.5 • ) (Bosilovich et al, 2015).…”
Section: Iwv From Nwmmentioning
confidence: 99%